Aberrant DNA hypermethylation of SDHC: a novel mechanism of tumor development in Carney triad - Haller, Florian; Moskalev, Evgeny; Faucz, Fabio R.; Barthelmeß, Sarah; Wiemann, Stefan; Bieg, Matthias; Assie, Guillaume; Bertherat, Jerome; Schaefer, Inga-Marie; Otto, Claudia; Rattenberry, Eleanor; Maher, Eamonn R.; et al. (Endocrine-Related Cancer, 2014)
Carney triad (CT) is a rare condition with synchronous or metachronous occurrence of gastrointestinal stromal tumors (GISTs), paragangliomas (PGLs), and pulmonary chondromas in a patient. In contrast to Carney-Stratakis syndrome (CSS) and familial PGL syndromes, no germline or somatic mutations in the succinate dehydrogenase (SDH) complex subunits A, B, C, or D have been found in most tumors and/or patients with CT. Nonetheless, the tumors arising among patients with CT, CSS, or familial PGL share a similar morphology with loss of the SDHB subunit on the protein level. For the current study, we employed massive parallel bisulfite sequencing to evaluate DNA methylation patterns in CpG islands in proximity to the gene loci of all four SDH subunits. For the first time, we report on a recurrent aberrant dense DNA methylation at the gene locus of SDHC in tumors of patients with CT, which was not present in tumors of patients with CSS or PGL, or in sporadic GISTs with KIT mutations. This DNA methylation pattern was correlated to a reduced mRNA expression of SDHC, and concurrent loss of the SDHC subunit on the protein level. Collectively, these data suggest epigenetic inactivation of the SDHC gene locus with functional impairment of the SDH complex as a plausible alternate mechanism of tumorigenesis in CT.
EVALuna2:6647